The - Bullock, Richard H. (W.W. Norton & Company, 2014)
The Little Seagull Handbook offers the kind of succinct advice students need about grammar, punctuation, documentation, and the writing process―an in addition, it covers the kinds of writing they are most often assigned―reports, analyses, narratives, and more. The second edition includes unique help for students whose primary language is not English. Available in two versions―with and without exercises